Interbank market integration, loan rates, and firm leverage - Steven Ongena; Alexander Popov (European Central Bank (ECB), 2010)
We study the effect of interbank market integration on small firm finance in the build-up to the 2007-2008 financial crisis. We use a comprehensive data set that contains contract terms on individual loans to 6,047 firms across 14 European countries between 1998:01 and 2005:12. We account for the selection that arises in the loan request and approval process. Our findings imply that integration of interbank markets resulted in less stringent borrowing constraints and in substantially lower loan rates. The decrease was strongest in markets with competitive banking sectors. We also find that in the most rapidly integrating markets, firms became substantially overleveraged during the build-up to the crisis.
Keywords: E51; G15; G21; G34; 330; Bank competition; firm leverage; Interbank markets; loan rates; selection; Geldmarkt; Marktintegration; Kreditgeschäft; Wettbewerb; Kapitalstruktur; EU-Staaten